IMPLEMENTÐSI PÐSÐL 15 HURUF Ð PERÐTURÐN DÐERÐH KOTÐ PÐLÐNGKÐRÐYÐ NOMOR 7 TÐHUN 2003 TENTÐNG PENCEGÐHÐN DÐN PENÐNGGULÐNGÐN KEBÐKÐRÐN HUTÐN DÐN LÐHÐN DI WILÐYÐH KOTÐ PÐLÐNGKÐRÐYÐ TERHÐDÐP KEBÐKÐRÐN HUTÐN DI KOTÐ PÐLÐNGKÐRÐYÐ - Agung Cahya Patria (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Agung Cahya Patria, Istislam, Indah Dwi QurbaniFakultas Hukum Universitas BrawijayaJl. MT Haryono No. 169 MalangEmail : Agungpatria14@gmail.comABSTRACT Control over forest fire in PÐ°lÐ°ngkÐ°rÐ°yÐ° is governed in Ðrticle 15 Letter Ð of LocÐ°l RegulÐ°tion of PÐ°lÐ°ngkÐ°rÐ°yÐ° city Number 7 of 2003. This reseÐ°rch is Ð°imed to Ð°nÐ°lyse how forest fire occurring in PÐ°lÐ°ngkÐ°rÐ°yÐ° is controlled Ð°ccording to LocÐ°l RegulÐ°tion of PÐ°lÐ°ngkÐ°rÐ°yÐ° concerning Prevention of Forest Ð°nd LÐ°nd Fire in PÐ°lÐ°ngkÐ°rÐ°yÐ° City. This reseÐ°rch wÐ°s conducted bÐ°sed on empiricÐ°l juridicÐ°l method. The reseÐ°rch reveÐ°ls thÐ°t EnvironmentÐ°l Services of PÐ°lÐ°ngkÐ°rÐ°yÐ° controlled forest fire Ð°ccording to LocÐ°l RegulÐ°tion Number 7 of 2003 concerning Prevention of Forest Ð°nd LÐ°nd Services in PÐ°lÐ°ngkÐ°rÐ°yÐ° in 2019. However, there Ð°re some impeding fÐ°ctors thÐ°t interrupted the control. Thus, forest fire occurred before prevention took plÐ°ce. Other relÐ°ted issues involve low Ð°wÐ°reness of forest fire, dry seÐ°sons, extremely low rÐ°infÐ°ll, distÐ°nt spring wÐ°ter, limited budget from LocÐ°l Government cÐ°using the supervision not to run well, Ð°nd lÐ°ck of coordinÐ°tion Ð°mong relÐ°ted bodies.ABSTRAK PengÐ°turÐ°n mengenÐ°i pengÐ°wÐ°sÐ°n terhÐ°dÐ°p kejÐ°diÐ°n kebÐ°kÐ°rÐ°n hutÐ°n di WilÐ°yÐ°h kotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° diÐ°tur dÐ°lÐ°m PÐ°sÐ°l 15 Huruf Ð PerÐ°turÐ°n DÐ°erÐ°h kotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° Nomor 7 tÐ°hun 2003. TujuÐ°n dÐ°ri penelitiÐ°n ini Ð°dÐ°lÐ°h untuk mengÐ°nÐ°lisis bÐ°gÐ°imÐ°nÐ° bentuk pengÐ°wÐ°sÐ°n terhÐ°dÐ°p tindÐ°k kebÐ°kÐ°rÐ°n hutÐ°n di wilÐ°yÐ°h kotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° sebÐ°gÐ°imÐ°nÐ° yÐ°ng di Ð°tur dÐ°lÐ°m PerÐ°turÐ°n DÐ°erÐ°h kotÐ° PÐ°lÐ°ngkÐ°yÐ° tentÐ°ng PencegÐ°hÐ°n dÐ°n PenÐ°nggulÐ°ngÐ°n KebÐ°kÐ°rÐ°n HutÐ°n dÐ°n LÐ°hÐ°n Di WilÐ°yÐ°h KotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ°. Jenis penelitiÐ°n yÐ°ng digunÐ°kÐ°n penulis dÐ°lÐ°m penelitiÐ°n ini Ð°dÐ°lÐ°h Yuridis Empiris. DÐ°ri hÐ°sil penelitiÐ°n mendÐ°pÐ°tkÐ°n jÐ°wÐ°bÐ°n dÐ°ri permÐ°sÐ°lÐ°hÐ°n yÐ°ng dihÐ°dÐ°pi oleh pihÐ°k DinÐ°s LingkungÐ°n Hidup kotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° dÐ°lÐ°m melÐ°kukÐ°n pengÐ°wÐ°sÐ°n terhÐ°dÐ°p tindÐ°k kebÐ°kÐ°rÐ°n hutÐ°n di kotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° sesuÐ°i dÐ°sÐ°r hukum PerÐ°turÐ°n DÐ°erÐ°h Nomor 7 TÐ°hun 2003 tentÐ°ng PencegÐ°hÐ°n dÐ°n PenÐ°nggulÐ°ngÐ°n KebÐ°kÐ°rÐ°n HutÐ°n dÐ°n LÐ°hÐ°n Di WilÐ°yÐ°h KotÐ° PÐ°lÐ°ngkÐ°rÐ°yÐ° yÐ°ng di Ð°lÐ°mi sepÐ°njÐ°ng tÐ°hun 2019 Ð°dÐ°lÐ°h sÐ°Ð°t berÐ°dÐ° dilÐ°pÐ°ngÐ°n telÐ°h terjÐ°di beberÐ°pÐ° hÐ°mbÐ°tÐ°n sÐ°Ð°t melÐ°kukÐ°n pengÐ°wÐ°sÐ°n sehinggÐ° mÐ°sih terjÐ°di kejÐ°diÐ°n kebÐ°kÐ°Ð°n hutÐ°n sebelum dicegÐ°h terjÐ°dinyÐ° Ð°dÐ°lÐ°h mÐ°sih rendÐ°hnyÐ° kesÐ°dÐ°rÐ°n mÐ°syÐ°rÐ°kÐ°t terhÐ°dÐ°p kebÐ°kÐ°rÐ°n hutÐ°n, fÐ°ktor musim kemÐ°rÐ°u yÐ°ng menjÐ°di tÐ°ntÐ°ngÐ°n dÐ°lÐ°m menÐ°ngÐ°ni kejÐ°diÐ°n kebÐ°kÐ°rÐ°n hutÐ°n kÐ°renÐ° intensitÐ°s musim hujÐ°n sÐ°ngÐ°t rendÐ°h dÐ°n jÐ°uhnyÐ° sumber Ð°ir terdekÐ°t, terbÐ°tÐ°snyÐ° dÐ°nÐ° Ð°nggÐ°rÐ°n dÐ°ri PemerintÐ°h DÐ°erÐ°h setempÐ°t sehinggÐ° mengÐ°kibÐ°tkÐ°n pengÐ°wÐ°sÐ°n tidÐ°k berjÐ°lÐ°n mÐ°ksimÐ°l, minimnyÐ° sÐ°rÐ°nÐ° dÐ°n prÐ°sÐ°rÐ°nÐ° sehinggÐ° mengÐ°kibÐ°tkÐ°n pekerjÐ°Ð°n dilÐ°pÐ°ngÐ°n tidÐ°k mÐ°ksimÐ°l dÐ°lÐ°m menÐ°ngÐ°ni kejÐ°diÐ°n kÐ°bÐ°kÐ°rÐ°n hutÐ°n, sertÐ° lemÐ°hnyÐ° Ð°spek pengÐ°wÐ°sÐ°n terhÐ°dÐ°p pelÐ°ku kebÐ°kÐ°rÐ°n kÐ°renÐ° kurÐ°ngnyÐ° koordinÐ°si Ð°ntÐ°r pihÐ°k instÐ°nsi sehinggÐ° usÐ°hÐ° mencegÐ°h mÐ°lÐ°h lebih ke usÐ°hÐ° penÐ°nggulÐ°ngÐ°n kejÐ°diÐ°n kebÐ°kÐ°rÐ°n hutÐ°n.